2013
DOI: 10.1039/c3ra42609b
|View full text |Cite
|
Sign up to set email alerts
|

A self-assembled nanostructured material with photosensitising properties

Abstract: Using a combination of molecular modelling and spectroscopic experiments, the naturally-occurring pharmacologically active hypericin compound is shown to form a stable 1 : 1 complex with apomyoglobin that preserves its fluorescence and singlet oxygen photosensitising properties. The binding equilibrium constant has been determined as K a = (2.4 ¡ 0.5) 6 10 5 M 21 , equivalent to a dissociation constant K d = 4.2 ¡ 0.8 mM. The kinetic details of singlet oxygen production have been characterised and indicate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 32 publications
4
47
0
Order By: Relevance
“…When Hyp is dissolved in the presence of 2β-LG, its absorption spectrum shows sharper bands instead and, most importantly, the fluorescence emission increases substantially and becomes structured ( Figure 3B). These facts indicate that Hyp is located in a substantially less polar environment than water, as previously observed with apomyoglobin and human serum albumin (Miskovsky et al, 1998;Das et al, 1999;Comas-Barceló et al, 2013), as a result of binding to the protein. These conditions are a prerequisite for preservation of the singlet oxygen photosensitization via energy transfer from the Hyp triplet state.…”
Section: Spectroscopic Analysis Of Hyp Binding To β-Lgmentioning
confidence: 52%
See 3 more Smart Citations
“…When Hyp is dissolved in the presence of 2β-LG, its absorption spectrum shows sharper bands instead and, most importantly, the fluorescence emission increases substantially and becomes structured ( Figure 3B). These facts indicate that Hyp is located in a substantially less polar environment than water, as previously observed with apomyoglobin and human serum albumin (Miskovsky et al, 1998;Das et al, 1999;Comas-Barceló et al, 2013), as a result of binding to the protein. These conditions are a prerequisite for preservation of the singlet oxygen photosensitization via energy transfer from the Hyp triplet state.…”
Section: Spectroscopic Analysis Of Hyp Binding To β-Lgmentioning
confidence: 52%
“…Accordingly, the affinity of Hyp for 2β-LG can be evaluated by monitoring the fluorescence emission as a function of Hyp concentration ( Figure 3C). A model for the binding equilibrium Hyp + 2β-LG ⇆ 2β-LG-Hyp (Comas- Barceló et al, 2013) affords an association constant, K a = 1.40 ± 0.07 µM −1 , corresponding to a dissociation constant, K d = 0.71 ± 0.03 µM.…”
Section: Spectroscopic Analysis Of Hyp Binding To β-Lgmentioning
confidence: 99%
See 2 more Smart Citations
“…19 Among other carriers, proteins are highly biocompatible systems that warrant bioavailability of the PS. We recently demonstrated that the complex between Hyp and apomyoglobin (apoMb) is an effective photosensitizing agent for Gram positive bacteria, 20 with fluorescence properties that allow us to localize the PS with subdiffraction resolution on bacterial cells, using STED (Stimulated Emission Depletion) microscopy. 21 We also demonstrated the use of b-lactoglobulin (bLG) as a carrier for Hyp in aqueous solutions such as phosphate-buffered saline (PBS), with the advantage, relative to apoMb, that it could carry more Hyp molecules per protein unit.…”
Section: Introductionmentioning
confidence: 99%